A comparison of the quantitative anatomy of the bronchi in normal subjects, in status asthmaticus, in chronic bronchitis, and in emphysema. Issue 2 (March 1969) - Dunnill, M. S.; Massarella, G. R.; Anderson, J. A.
Abstract : The quantitative anatomy of the bronchi has been studied in sudden deaths in normal subjects, in deaths from status asthmaticus and chronic bronchitis, and in patients with emphysema. In the normal bronchi the observed range of values for the percentage volume of mucous glands was between 7·6 and 16·7. In the status asthmaticus group the mucous gland volume was greatly increased and in no case was there an overlap with the normal subjects. In the 19 cases of chronic bronchitis, two cases had values of 15·2 and 15·4% respectively, but all the others had values higher than the normal range and, in two instances, values of over 40% were obtained. The values obtained for mucous gland volume in the bronchi in emphysema were variable, approximately half being within the normal range. The bronchial smooth muscle accounted for 4·6±2·2% of the volume of the normal bronchial wall. The values obtained in chronic bronchitis and emphysema did not differ significantly from this but in those dying of status asthmaticus there was a very significant increase with a mean value of 11·9±3·36.